Is It Really more Blessed to Give than to Receive? A Consideration of Forgiveness and Perceived Health. Issue 1 (March 2016) - Bassett, Rodney L.; Carrier, Evan; Charleson, Katherine; Pak, Na Ra; Schwingel, Rachael; Majors, Alexandra; Pitre, Meredith; Sundlof-Stoller, Andrea; Bloser, Carol
There are several aspects to forgiveness. To this point, few studies have simultaneously considered the impact of all these different aspects, and none have considered the impact of all these aspects of forgiveness upon perceived physical health. Participants, ranging in age from 18 to 93, self-reported tendencies toward various types of dispositional forgiveness, well-being, and empathy. These individuals reported they were most inclined to seek forgiveness from others and feel forgiven by God. They were least inclined to self-forgive. A second study was conducted as a conceptual replication of the first study. Across both studies results suggested that the way granting forgiveness was operationalized mattered and that self-forgiveness was the most significant contributor to perceived physical health.